2022
DOI: 10.1108/ijlss-06-2022-0131
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap for product development based on design for six sigma method

Abstract: Purpose The Design For Six Sigma (DFSS) methodology is one of the most important to achieving excellence in an organization’s product development process. This paper aims to propose a roadmap for product development based on the DFSS for the consumer durables manufacturing industries. The proposed roadmap presents a systematic approach to the phases of the product development process, integrating the statistical techniques and quality tools that should be used in each phase. Design/methodology/approach This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…They propose methodologies for incorporating LM to develop sustainable products (Dahmani et al. , 2022), utilise statistical techniques and quality tools in different phases of the PDP (Francisco et al. , 2022) and explore the moderating role of LM in quality performance (Marodin et al.…”
Section: Current Literature On Industry 40 and Lean Manufacturing In ...mentioning
confidence: 99%
See 2 more Smart Citations
“…They propose methodologies for incorporating LM to develop sustainable products (Dahmani et al. , 2022), utilise statistical techniques and quality tools in different phases of the PDP (Francisco et al. , 2022) and explore the moderating role of LM in quality performance (Marodin et al.…”
Section: Current Literature On Industry 40 and Lean Manufacturing In ...mentioning
confidence: 99%
“…Throughout the phases of the PDP, integrating external knowledge with internal knowledge plays a crucial role in enhancing design quality and MP for new products, fostering synergy within the organisation (Benitez et al, 2022). Notably, several authors have suggested that LM principles can serve as catalysts for achieving superior market performance in the PDP (de Toledo et al, 2023;Dahmani et al, 2022;Francisco et al, 2022;Oliveira et al, 2022;Reis et al, 2021;Varl et al, 2020;Marodin et al, 2018). Therefore, the objective of our study is to investigate the potential positive association between LM and the various phases of the PDP, focussing on improving efficiency in terms of MP.…”
Section: Lean Manufacturing and Pdp Association With Market Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The Design For Six Sigma (hereinafter referred to as "DFSS") methodology and other "six sigma" methodologies (e.g. Lean Six Sigma) is one of the most important to achieving excellence in an organization's product development process (Francisco et al, 2022).…”
Section: Literature Introductionmentioning
confidence: 99%